1991
DOI: 10.1159/000293161
|View full text |Cite
|
Sign up to set email alerts
|

Advantage or Disadvantage of Episiotomy Compared with Spontaneous Perineal Laceration

Abstract: In a prospective clinical investigation of 2,144 deliveries, we elucidate the indications for episiotomy and how different methods of anesthesia affect the frequency of episiotomy and the perineal problems after episiotomy compared with those after spontaneous perineal laceration. We found a significantly higher infection rate (p < 0.001) and a longer healing period in the episiotomy group. These differences remain even if only primigravida or the indication, imminent perineal laceration, is studied. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
7

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(34 citation statements)
references
References 5 publications
(5 reference statements)
1
26
0
7
Order By: Relevance
“…The decreased rate of episiotomies and increased rate of perineal tears is consistent with findings from meta analyses (37,38). There is limited evidence that episiotomy carries an increased risk of side-effects, such as infection, perineal breakdown and pain, compared with perineal tear (39)(40)(41).…”
Section: Discussionsupporting
confidence: 80%
“…The decreased rate of episiotomies and increased rate of perineal tears is consistent with findings from meta analyses (37,38). There is limited evidence that episiotomy carries an increased risk of side-effects, such as infection, perineal breakdown and pain, compared with perineal tear (39)(40)(41).…”
Section: Discussionsupporting
confidence: 80%
“…In addition to the complex effects on the urological and reproductive systems during delivery, edema and pain in the perineum also made it difficult to urinate. Larsson, Platz-Christensen, Bergman, and Wallstersson (1991) investigated perineal laceration and pain after birth using a visual analog scale. Women with mediolateral episiotomies had more pain on the first and third days after birth than the natural laceration group and no laceration group.…”
Section: Predictive Factors For Purmentioning
confidence: 99%
“…The studies included analysis of APGAR scores, neonatal resuscitation or the need for intensive care admission. In the studies conducted by Larsson et al (1991), Thranov et al (1990), and Borgatta et al (1989), there was no difference found in the APGAR scores of the new born at 1 min or 5 min in the episiotomy group compared to those of the spontaneous laceration group.…”
Section: Prevention Of Damage To the Newborn/ Shortening Of The Seconmentioning
confidence: 87%